Piranômetro de equivalência elétrica com compensação analógica da temperatura ambiente - Dantas, Evandson Claude Seabra (2022)
Pyranometers are devices used to measure the incident radiation on a given surface. This type of device is used in several applications in the area of solar energy, UV treatment, atmospheric research, etc. Some of these devices are based on the principle of electrical equivalence, in which an electrical power is used, in a thermoelectric balance system, to estimate solar radiation. For this, a controller, analog or digital, balances the electrical power against the incident radiation so that a thermoresistive sensor remains at a constant temperature. This configuration provides several advantages such as a quick response and high resolution for estimating solar radiation, however, it ends up presenting some limitations when the ambient temperature varies, varying parameters such as sensitivity, useful output voltage, power consumption, among others. In this work, it is proposed to replace the configuration that keeps the sensor temperature constant for the constant temperature difference configuration. The proposal is formulated by modifying the architecture of the feedback Wheatstone bridge so that it works with a constant temperature difference. The implemented proposal is then validated through computer simulations in a SPICE environment and through field experiments. In this work, a prototype was developed and tested in 3 different climatic conditions, namely: clear sky, partly cloudy sky and cloudy sky. The results of this work point to a 5-fold improvement in the useful voltage range, a reduction in the influence of ambient temperature variation on the output voltage, a reduction in electrical consumption and an increase in sensitivity to incident radiation.